Clinical performance evaluation of an HIV Duo assay: From HIV screening to acute and non-acute HIV infection detection - Liu, Xin; Wu, Chongyang; Yuan, Yulin; Li, Dongdong; Lou, Jinli; Feng, Xia; Lu, Qiuwei; Wu, Rongcai; Chen, An-Jou; Tao, Chuanmin (Clinica chimica acta, 2025)
•The Elecsys® HIV Duo assay has demonstrated a high specificity of 99.91 % (95 % CI: 99.89 %, 99.93 %) and a high PPV of 0.8516 (95 % CI: 0.8225, 0.8776), indicating that the assay is suitable for primary HIV screening in China.•The median (IQR) of the numeric cut-off index (COI) ratios of the HIV Duo antibody (Ab) and antigen (Ag) results significantly differed among the subgroups of diagnosed HIV patients: Ag + Ab-, Ag-Ab+, and Ag + Ab+ (all P<0.05).•The Elecsys® HIV Duo assay can identify acute HIV patients with Western blot (WB) −/not able to define (ND) results by providing Ag + HIV Duo result. Therefore, integrating the assay into a novel laboratory HIV testing algorithm has the potential to enable early detection of acute HIV infections and facilitating treatment initiation. Evaluating the clinical performance of Elecsys HIV Duo assay for primary human immunodeficiency virus (HIV) screening and acute HIV infection detection. This study was conducted from April 2022 to April 2023 and involved two distinct populations. For the HIV screening population, three HIV Duo results [HIV Duo, HIV antigen (Ag), and HIV antibody (Ab)] in primary screening were obtained (January 2021 to June 2021). In the diagnosed HIV population, retrospective samples from November 2016 to March 2023 were measured. The HIV screening population included 111,383 samples from a real-world screening program. The assay demonstrated a specificity of 99.91 % (95 % CI: 99.89 %, 99.93 %) and a PPV of 0.8516 (95 % CI: 0.8225, 0.8776). Regarding the diagnosed HIV population, 836 HIV patients were enrolled, including 14 acute HIV infectious patients with only HIV Ag + and a Western Blot (WB) confirmation rate of 0 %. The median (IQR) of the numeric cut-off index (COI) ratios of HIV Duo Ab and Ag significantly differed among the Ag + Ab-, Ag-Ab+, and Ag + Ab + subgroups. The Elecsys HIV Duo assay is suitable for primary HIV screening and can be integrated into a novel laboratory HIV testing algorithm to improve acute HIV detection in Chinese clinical practice. Abbreviations: HIV, Human immunodeficiency virus; AIDS, acquired immunodeficiency syndrome; Ag, antigen; Ab, antibody; WB, Western Blot; COI, numeric cut-off index; CI, confidence interval; NAT, nucleic acid tests; EDC, electronic data capture systems; CDC, Chinese Centers for Disease Control and Prevention; IQR, interquartile range; PPV, positive predictive value; HCV, hepatitis C virus; HBV, hepatitis B virus; CI, confidence interval; ND, not able to define; F, female; M, male;